Aquaporin-6 Expression in the Cochlear Sensory Epithelium Is Downregulated by Salicylates. (12th January 2010) - Perin, Paola; Tritto, Simona; Botta, Laura; Fontana, Jacopo Maria; Gastaldi, Giulia; Masetto, Sergio; Tosco, Marisa; Laforenza, Umberto
Abstract : We characterize the expression pattern of aquaporin-6 in the mouse inner ear by RT-PCR and immunohistochemistry. Our data show that in the inner ear aquaporin-6 is expressed, in both vestibular and acoustic sensory epithelia, by the supporting cells directly contacting hair cells. In particular, in the Organ of Corti, expression was strongest in Deiters' cells, which provide both a mechanical link between outer hair cells (OHCs) and the Organ of Corti, and an entry point for ion recycle pathways. Since aquaporin-6 is permeable to both water and anions, these results suggest its possible involvement in regulating OHC motility, directly through modulation of water and chloride flow or by changing mechanical compliance in Deiters' cells. In further support of this role, treating mice with salicylates, which impair OHC electromotility, dramatically reduced aquaporin-6 expression in the inner ear epithelia but not in control tissues, suggesting a role for this protein in modulating OHCs' responses.